Pengaruh Dukungan Sosial Teman Sebaya dan Regulasi Diri Belajar Terhadap Resiliensi pada Siswa SMA Tunas Harapan Mandiri Rantau Prapat - Nita Permata Sari Siregar; Asih Menanti; Hasanuddin Hasanuddin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this study was to determine the effect of peer social support and self-regulation in learning on resilience. The population is 200 students with 3 classes and the sample is 166 with random sampling technique. The results of this study indicate that there is a significant positive effect between peer social support on resilience, where the coefficient rx1y = 4.382 with p = 0.000, this means that the better peer social support, the better the resilience. The coefficient of r squared peer social support with the dependent variable of resilience is r2 = 4.382. This shows that resilience is formed by peer social support with a contribution of 12.80%. In the variable of self-regulation in learning with resilience there is also a significant positive relationship where the coefficient rx2y = 18,072 with p = 0.000, this means that the better self-regulation in learning, the better resilience. The coefficient of r squared self-regulation in learning with the dependent variable resiliency is r2 = 0.870. This shows that resilience is formed by self-regulation in learning with a contribution of 67.10%. Similar results came from the variables of peer social support and self-regulation in learning with a significant positive influence resiliency where the coefficient r = 0.894 with p = 0.000 means p <0.010. The determinant coefficient (r2) of the relationship between the predictors of peer social support, self-regulation in learning with the dependent variable resilience is r2 = 0.799. This shows that resilience is formed by self-regulation in learning and peer social support together with a contribution of 79.90%.